Analysis of the clinical efficacy of “dynamic hook technique” combined with the Allgower-Donati suture method in the surgical incision for calcaneal fractures - Liu, Bo; Ma, Long; Xiao, Dawei; Chen, Cheng; Zeng, Hui; Wang, Honghai; Zhang, Bowen; Wu, Gangqiang; Yu, Haiyang (Frontiers in Surgery, 2025)
ObjectivesTo analyze the clinical outcomes of “dynamic hook technique” combined with the Allgöwer-Donati suture technique in reducing incisional complications and Incisional pain after calcaneal fracture surgery.MethodsTotally, 93 patients with calcaneal fractures who underwent open reduction and internal fixation were included and divided into control and observation groups. In the observation group, the flap was elevated using the “dynamic hook technique”, while in the control group, the flap was elevated using the static Kirschner needle lifting technique. The flap in the two groups were sutured using the Allgöwer-Donati sutures. Postoperative complications, including tension blisters surrounding the incision, necrosis of the incision flap, and the steel plate exposure were analyzed. The Visual Analog Scale (VAS) was utilized to assess postoperative incision pain at 3 days, 1 and 2 weeks post-surgery. All patients were followed up for a duration of 3–6 months, with suture removal occurring 2–3 weeks postoperatively.ResultsThe incidence of complications was significantly lower in the observation group than the the control group (4.5% vs. 18.4%, P < 0.05). The patients in the observation group had significantly lower VAS pain scores at each time point after surgery when compared to the control group (P < 0.05).ConclusionThe combination of the “dynamic hook technique” and the Allgöwer-Donati suture is effective in preventing incisional complications and alleviating postoperative pain after open reduction and internal fixation for calcaneal fractures.